Wisdom's little sister : studies in medieval & Renaissance Jewish political thought - Melamed, Abraham, 1944- (Emunot., 2012)
As a recently established field of Jewish thought, Jewish political philosophy has made increasingly frequent appearances in recently edited histories of Jewish philosophy. Following the pioneering efforts of Leo Strauss, Ralph Lerner and Daniel Elazar, among others, Jewish political philosophy gained its proper place alongside ethics and metaphysics in the study of the history of Jewish philosophy. This volume is another manifestation of this welcomed development. Consisting of selected papers published in English over the last thirty years, Wisdoms Little Sister concentrates on the Medieval and Renaissance periods, from Sa'adiah Gaon in the tenth century to Spinoza in the seventeenth century. These were the formative periods in the development of Jewish political philosophy, when Jewish scholars, versed in the canonical Jewish sources (biblical and rabbinic), encountered Greek political philosophy as transmitted by Muslim philosophers such as Alfarabi, Ibn Bajja and Averroes. In combining Greek, Jewish and Muslim thought, these scholars are the originators of what we now know as Jewish political philosophy.